Public Perceptions of the Police During COVID-19: A Cross-National Analysis - Chenane, Joselyne L. (Criminal justice review, 2024)
Using cross-national data collected during the pandemic, this study examines factors influencing public willingness to obey and cooperate with police during the COVID-19 pandemic. Data for the study were garnered using web-based surveys, which yielded about 500 participants from the U.S., India, Brazil, Kenya, and several European countries. OLS results revealed that police legitimacy remains a crucial predictor of public willingness to obey and cooperate with the police. However, fears experienced during the pandemic failed to directly predict public's obligation to obey the police and their willingness to cooperate with the police. Interestingly, fear had an indirect effect on the relationship between police legitimacy and the obligation to obey and cooperate with the police. Conceptualizations of police legitimacy should continue to be tested, alternative versions of surveying without the limitations of COVID-19 should be undertaken, and attempts to understand more local environments should be made.